6
$\begingroup$

I'm trying to figure out a way to solve this equation:

$$\sqrt[3]{5x+7}-\sqrt[3]{5x-12}=1.$$

I tried to cube both sides, but I ended up with an equation looking like this:

$$\sqrt[3]{(5x-12)(5x+7)}(\sqrt[3]{5x-1}-\sqrt[3]{5x+7})=-6.$$

At this point I'm out of stuff to do. Any help would be appreciated. Thanks in advance.

$\endgroup$
  • 1
    $\begingroup$ substitute $y^3=5x+7$ so that you have only one root $\endgroup$ – Exodd Apr 23 '17 at 20:07
  • $\begingroup$ you 'parker-squared' it $\endgroup$ – Kartik Apr 24 '17 at 3:23
2
$\begingroup$

Following up on OP's "almost-there" attempt (and correcting the $-1\color{red}{2}\,$ in the second equation):

$\sqrt[3]{5x+7}-\sqrt[3]{5x-12}=1 \tag{1}$

i tried to cube both sides, but i ended up with an equation looking like this:

$\sqrt[3]{(5x-12)(5x+7)}(\sqrt[3]{5x-1\color{red}{2}}-\sqrt[3]{5x+7})=-6 $

The rightmost factor is $-1$ per the original equation $(1)\,$, which leaves:

$$-\sqrt[3]{(5x-12)(5x+7)}=-6 \tag{2}$$

Then the numbers $\,\sqrt[3]{5x+7}\,$ and $\,-\sqrt[3]{5x-12}\,$ have sum $\,1\,$ per $(1)\,$, and product $\,-6\,$ per $(2)\,$, so they are the roots of the quadratic $\,t^2-t-6=0 \iff t \in \{-2, 3\}\,$:

  • $\sqrt[3]{5x+7} = -2 \iff 5x +7 = -8 \iff x = -3$

  • $\sqrt[3]{5x+7} = 3 \iff 5x + 7 = 27 \iff x = 4$

$\endgroup$
  • 1
    $\begingroup$ what a wonderful way to do it. thank you very much. $\endgroup$ – j.jamesjonas Apr 24 '17 at 0:49
7
$\begingroup$

Put $a = \sqrt[3]{5x+7}, b = \sqrt[3]{5x-12}\implies a - b = 1, a^3 - b^3 =19\implies a^2+ab+b^2 = \dfrac{a^3-b^3}{a-b} = \dfrac{19}{1} = 19\implies (a-b)^2+3ab = 19\implies 1^2+3ab = 19 \implies ab = 6\implies (b+1)b = 6\implies b^2+b-6 = 0\implies (b+3)(b-2)=0\implies b = 2, -3\implies 5x-12 = 2^3, (-3)^3 = 8,-27\implies 5x = 20, -15\implies x = 4, -3.$

$\endgroup$
  • $\begingroup$ Nicely done. (+1) $\endgroup$ – Mark Viola Apr 23 '17 at 20:28
  • $\begingroup$ very nice way to solve it. thanks $\endgroup$ – j.jamesjonas Apr 23 '17 at 20:32
5
$\begingroup$

Before cubing, separate your roots:

$$\sqrt[3]{5x+7}=\sqrt[3]{5x-12}+1$$

Now cube:

$$5x + 7 = 5x - 12 + 3\sqrt[3]{5x-12}^2 + 3\sqrt[3]{5x-12} + 1$$

Simplify:

$$ \sqrt[3]{5x-12}^2 + \sqrt[3]{5x-12} - 6 = 0$$

Solve for $\sqrt[3]{5x-12}$ (it is a quadratic equation). Finally solve to $x$.

$\endgroup$
  • $\begingroup$ This is the way I would have proceeded. (+1) $\endgroup$ – Mark Viola Apr 23 '17 at 20:29
  • $\begingroup$ helped me a lot. thanks $\endgroup$ – j.jamesjonas Apr 23 '17 at 20:29
4
$\begingroup$

Let's see. We have

$$\sqrt[3]{5x+7}-\sqrt[3]{5x-12}=1$$

now set $x=y+\frac12$. Then

$$\sqrt[3]{5y+\tfrac{19}2}-\sqrt[3]{5y-\tfrac{19}2}=1$$

Now cubing yields

$$19-3\sqrt[3]{(5y)^2-(\tfrac{19}2)^2}\left(\sqrt[3]{5y+\tfrac{19}2}-\sqrt[3]{5y-\tfrac{19}2}\right)=1$$

which rewrites to

$$\sqrt[3]{(5y)^2-(\tfrac{19}2)^2}=6$$

Which is easy to solve, $25y^2=6^3+(\frac{19}2)^2$ or $y=\pm \frac 72$. Now we conclude $x=4$ or $x=-3$.

$\endgroup$
  • $\begingroup$ wow. i could never imagine that you could do something like that. $\endgroup$ – j.jamesjonas Apr 23 '17 at 20:33
  • $\begingroup$ I always tend to make expressions as symmetric as I can. In this case, that turns out to be very useful $\endgroup$ – vrugtehagel Apr 23 '17 at 20:56
2
$\begingroup$

Actually, there is a nice, generic solution to equations of this type, namely equations in the form

$$\sqrt[3]{f(x)}+\sqrt[3]{g(x)} = C,$$

especially if $f(x)$ and $g(x)$ sum to a constant.

Cubing and rearranging, we get

$$f(x) + g(x) + 3C\sqrt[3]{f(x)g(x)}=C^3,$$

or

$$\sqrt[3]{f(x)g(x)} = \frac{C^3-f(x)-g(x)}{3C}.$$

Cubing again, we get

$$f(x)g(x) = \frac{(C^3-f(x)-g(x))^3}{27C^3}.$$

If $f(x)$ and $g(x)$ are linear in $x$, this is a cubic equation. But if $f(x)+g(x)=A$ const., we get

$$f(x)[A-f(x)] = \frac{(C^3-A)^3}{27C^3},$$

or

$$f(x)^2 - Af(x) + \left[\frac{(C^3-A)}{3C}\right]^3 = 0,$$

which is quadratic in $f(x)$.

In the specific example, $f(x)=5x+7$, $g(x)=-5x+12$, $A=f(x)+g(x)=19$, $C=1$, and we get

$$f(x)^2 - 19f(x) - 216=0,$$

which yields $f(x)=5x+7=27$ or $f(x)=5x+7=-8$, i.e., $x=4$ or $x=-3$.

$\endgroup$
  • $\begingroup$ very plainly explained. thank you for spending your time on this. $\endgroup$ – j.jamesjonas Apr 24 '17 at 1:26
1
$\begingroup$

$$a=\sqrt[3]{5x+7},b=\sqrt[3]{5x-12}\\a-b=1\\(a-b)^3=1\\a^3-3a^2b+3ab^2-b^3=1\\a^3-b^3-3ab(a-b)=1\\a^3-b^3-3ab=1\\5x+7-5x+12-3\sqrt[3]{5x+7}\sqrt[3]{5x-12}=1\\-3\sqrt[3]{5x+7}\sqrt[3]{5x-12}=-18\\\sqrt[3]{5x+7}\sqrt[3]{5x-12}=6\\(5x+7)(5x-12)=216\\25x^2-60x+35x-84=216\\25x^2-25x-300=0\\x^2-x-12=0\\x_1=4,x_2=3$$

$\endgroup$
  • $\begingroup$ I like it better this way. $\endgroup$ – Iti Shree Apr 23 '17 at 20:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.